2022
DOI: 10.1017/ice.2022.34
|View full text |Cite
|
Sign up to set email alerts
|

Examining drivers of coronavirus disease 2019 (COVID-19) vaccine hesitancy among healthcare workers

Abstract: Objective: To assess characteristics and perceptions associated with vaccine hesitancy among healthcare workers in order to increase COVID-19 vaccine uptake in this population. Design: Cross-sectional quantitative survey Setting: Southwest Virginia Participants: A convenience sample of 2,720 employees of a not-for-profit healthcare system Methods: Between March 15-29, 2021, we conducted an Internet-based survey. Our questionnaire asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Pregnant or trying to become pregnant HCWs had higher rates of vaccine hesitancy; pregnant women were six times more likely to delay and women trying to become pregnant were three times more likely [156]. Concerns about fertility have also been observed in men [157]. However, a study of HCWs in New York did not find differences in hesitancy among different age groups of women, suggesting that higher rates of female vaccine hesitancy may not be simply explained by concerns over fertility, pregnancy, or breastfeeding [90].…”
Section: Concerns About Safety and Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant or trying to become pregnant HCWs had higher rates of vaccine hesitancy; pregnant women were six times more likely to delay and women trying to become pregnant were three times more likely [156]. Concerns about fertility have also been observed in men [157]. However, a study of HCWs in New York did not find differences in hesitancy among different age groups of women, suggesting that higher rates of female vaccine hesitancy may not be simply explained by concerns over fertility, pregnancy, or breastfeeding [90].…”
Section: Concerns About Safety and Efficacymentioning
confidence: 99%
“…Others contend that vaccination should not be required or is not necessary for those who have already contracted COVID-19 [110,142]. This may be due to feeling protected from COVID-19 due to previous illness or because those who are more likely to contract COVID-19 had fewer health-protective behaviors in the first place [157]. One study of over 65,000 US HCWs noted a lower vaccination rate among those who had previously been infected with COVID-19 (OR, 0.55; 95% CI, 0.51-0.58, p < 0.0001) [227].…”
Section: Vaccination Unnecessarymentioning
confidence: 99%
“…One group amongst whom COVID-19 vaccine hesitancy has been especially problematic over the course of the pandemic is healthcare workers (HCWs). Studies of HCWs in various contexts found degrees of hesitancy that ranged between 15% and 30% [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Demographic factors associated with COVID-19 vaccine hesitancy amongst HCWs included younger age [ 13 , 15 , 16 , 20 , 21 , 22 , 23 ], female sex [ 13 , 16 , 17 , 18 , 19 , 21 , 24 , 25 , 26 , 27 ], African American race [ 15 , 16 , 17 , 26 , 27 ], and lower educational attainment [ 17 , 23 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of HCWs in various contexts found degrees of hesitancy that ranged between 15% and 30% [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Demographic factors associated with COVID-19 vaccine hesitancy amongst HCWs included younger age [ 13 , 15 , 16 , 20 , 21 , 22 , 23 ], female sex [ 13 , 16 , 17 , 18 , 19 , 21 , 24 , 25 , 26 , 27 ], African American race [ 15 , 16 , 17 , 26 , 27 ], and lower educational attainment [ 17 , 23 , 27 ]. Role in healthcare has also been found to be predictive of vaccine hesitancy, with nurses consistently displaying higher levels of hesitancy compared to physicians [ 13 , 15 , 16 , 17 , 18 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently limited information [15] regarding how COVID-19 vaccine hesitancy among HCWs may depend on the sociodemographic characteristics of the HCW, such as race/ethnicity, income, and education. Some studies have shown that COVID-19 vaccination acceptance is higher among HCWs identifying as white or Asian [10,16], while Black HCWs may be the most hesitant, followed by Hispanic/Latino HCWs [17].…”
Section: Introductionmentioning
confidence: 99%